The Effects of Vitamin K1 and Warfarin on Prothrombin Expression in Human Hepatoblastoma (HepG2) Cells - Jamison, C Scott; Burkey, Bryan F; Degen, Sandra J Friezner (Thrombosis and Haemostasis, 1992)
Cultures of human hepatoblastoma (HepG2) cells were treated with vitamin K1 or warfarin and prothrombin antigen and mRNA levels were determined. With 3 and 6 h of 10 µg vitamin K1 treatment secreted prothrombin antigen levels, relative to total secreted protein levels, were increased 1.5-fold and 2.1-fold, respectively, over ethanol-treated control levels as determined by an enzyme-linked immunosorbent assay. Dose-response analysis with 3 h of 25 µg/ml vitamin K1 treatment demonstrated a maximal increase of 2.0-fold in secreted prothrombin antigen levels, relative to total secreted protein levels, over ethanol-treated control levels. Pulse-chase analysis with 35S-methionine and immunoprecipitation of 35S-labelled prothrombin demonstrated that, with vitamin K1 treatment (25 µg/ml, 3 h), the rate of prothrombin secretion increased approximately 2-fold and the total amount (intra- and extracellular) of prothrombin synthesized increased approximately 50% over ethanol-treated control levels. Warfarin treatment (1, 5, or 10 µg/ml, 24 h) resulted in decreases in secreted prothrombin antigen levels, relative to total protein levels to approximately 85%, 87% or 81% of ethanol-treated control levels. Analysis of total RNA isolated from these cultures by Northern and solution hybridization techniques demonstrated that prothrombin mRNA was approximately 2.1 kb and that neither vitamin K1 nor warfarin treatment affected the quantity of prothrombin mRNA (ranging from 240–350 prothrombin mRNA molecules per cell). These results demonstrate that vitamin K1 and warfarin, in addition to effects on γ-carboxylation, affect prothrombin synthesis post-transcriptionally, perhaps influencing translation, post-translational processing and/or secretion mechanisms.